Triangular Function Method is Adopted to Solve Nonlinear Stochastic It o^–Volterra Integral Equations - Guo Jiang; Dan Chen; Fugang Liu (Discrete Dynamics in Nature and Society)
This article presents the numerical solutions of nonlinear stochastic It o^–Volterra integral equations by using the basis function method under the global Lipschitz condition. Integral operator matrixes of triangular functions are used to convert the nonlinear stochastic integral equations into a system of algebraic equations. Meanwhile, we gain the error of the current method, and it is demonstrated that the error accuracy of this method is higher than that of the BPFs. In the end, the feasibility, accuracy, and validity of the current method are demonstrated by numerical results.